The Efficacy Of Isopropyl Amine Glyphosate 165 Sl Herbicide Effect On Weed Control Of Coconut Cultivation - Doni Hariandi; Ryan Budi Setiawan; Khairur Rizki (Jurnal Riset Perkebunan, 2023)
Coconut plants are an important commodity for Indonesian people. In the cultivation process, coconut plants need a suitable environment for growth and production. One of the problems in cultivation is weeds. Weeds have a negative impact on cultivated plants, therefore appropriate control measures are needed. So far, the most effective weed control is chemical methods using herbicides. One of the herbicides that can be used is the herbicide with isopropyl amine glyphosate 165 SL. The aim of the experiment was to determine the efficacy of the herbicide isopropyl amine glyphosate 165 SL for controlling weeds in coconut cultivation was conducted from February to June 2022 at Pariaman City, West Sumatra Province. The experimental units were laid out according to a Randomized Block Design with 7 treatments and 3 groups as replications. The treatment was herbicide isopropyl amine glyphosate 165 SL at doses of 3.50 l ha-1, 5.25 l ha-1, 7.00 l ha-1, 8.75 l ha-1, 10.00 l ha-1, manual weeding and control (without weeding). The results of the research show that (1) The herbicide isopropyl amine glyphosate 165 SL can generally control weeds in coconut cultivation up to 12 weeks after application because the weed biomass in the treatment plot is relatively the same as manual weeding and is lighter than the control; (2) Herbicide isopropyl amine glyphosate 165 SL with a dose range of 3.50 l/ha – 10.50 l ha-1 up to 6 weeks after application does not show symptoms of phytotoxicity in coconut plants.